(untitled) (CIPEEX, 2025)
Introduction: Food and nutritional insecurity remains a significant and complex challenge in Brazil, disproportionately affecting low-income communities. This condition, which goes beyond the mere lack of food scarcity, is intrinsically linked to socioeconomic disparities that limit access to fresh and nutritious foods. As a result, vulnerable populations often adopt inadequate eating patterns, perpetuating the cycle of food insecurity. The relationship between diet and health in these communities is multifaceted and paradoxical: while undernutrition persists, the nutritional transition also favors the excessive consumption of ultra-processed foods, associated with the rising prevalence of chronic non-communicable diseases such as diabetes and hypertension. Objective: To assess the perception, eating practices, and multifaceted impacts of food insecurity in low-income communities in the city of Anápolis, Goiás, analyzing their direct and complex relationship with nutritional status and overall health. Methods: A mixed cross-sectional study will be conducted, combining quantitative and qualitative approaches with stratified cluster sampling. The research will take place in Primary Health Care Units (UBS) of Anápolis-GO, specifically in Jardim Esperança, Paraíso, and Bairro de Lourdes. The sample will include 102 participants, 34 from each unit, comprising families with children under 18 and/or older adults over 60, considered the most vulnerable groups. Data collection will be carried out in person, using questionnaires and anthropometric assessment. The Brazilian Household Food Insecurity Scale (EBIA) will be applied to measure household food security. Additionally, semi-structured questionnaires will be used to characterize eating practices, nutritional knowledge, and socioeconomic and cultural barriers. Anthropometric evaluation will include weight, height, waist, and hip circumference, following reference standards from WHO and the Brazilian Ministry of Health. Results: It is expected that the findings aims to accurately identify the prevalence of food insecurity in the studied communities and its association with nutritional status, including cases of undernutrition, obesity, and chronic diseases. Furthermore, the study will allow mapping of cultural perceptions, beliefs, and food myths, as well as socioeconomic barriers that hinder access to nutritious and healthy foods, providing updated and specific data on food insecurity in Anápolis. Conclusion: The results of this project are expected to support the development of more effective public policies and nutritional education programs tailored to local needs. The ultimate goal is to promote healthier and more sustainable food choices, directly contributing to the improvement of health and well-being among the vulnerable population of Anápolis-GO and helping to reduce the negative impacts of food insecurity in the vulnerable community